The Effect of Restructuring, Industrial Sector and Loan Nominal on Asset Quality of MSME Debtors Affected by the Covid-19 Pandemic - Fitria Sarah; Rida Rahim; Fajri Adrianto (Enrichment : Journal of Management, 2022)
COVID-19 has an impact on SMEs. Therefore BNI is making efforts to save credit.in.the.form of credit restructuring.for.debtors who are caused by COVID-19. The aim of this study is to determine the effect of restructuring, nominal loan size, and the business industry sector on the Quality of MSME Debtor Loan Assets in West Sumatra Province, Riau Province and Riau Islands Province. this research is quantitative.research with the object of research namely PT. Bank Negara Indonesia (Persero) Tbk. the.sample in.this.study was 210 indicators taken using a purposive sampling technique. The collected data is then analyzed statistically with.SPSS. The results of this.study shows that the Provision of Restructuring has a significant effect on the Quality of Debtor Assets at PT Bank Negara Indonesia (Persero). Then, the Industrial Sector partially has a significant effect on the Quality of Debtor Assets at PT Bank Negara Indonesia (Persero) Tbk. The nominal loan partially has a significant.effect.on the quality.of theldebtor's assets at PT Bank Negara Indonesia (Persero) Tbk. Gender moderates the relationship between Restructuring Grants and Debtor Asset Quality at PT Bank Negara Indonesia (Persero) Tbk RegionallOffice 02. However, gender partially does notlsignificantlylmoderate the relationship between the Industrial Sector and Debtor Asset Quality at PT Bank Negara Indonesia (Persero) Tbk. Gender moderates the relationship between the loan nominal andlthe quality of the debtor'slassets at PT Bank Negara Indonesia (Persero) Tbk.